Fluid mechanics of nodal flow due to embryonic primary cilia. - Smith, D; Blake, JR; Gaffney, E (2008)
Breaking of left-right symmetry is crucial in vertebrate development. The role of cilia-driven flow has been the subject of many recent publications, but the underlying mechanisms remain controversial. At approximately 8 days post-fertilization, after the establishment of the dorsal-ventral and anterior-posterior axes, a depressed structure is found on the ventral side of mouse embryos, termed the ventral node. Within the node, 'whirling' primary cilia, tilted towards the posterior, drive a flow implicated in the initial left-right signalling asymmetry. However, the underlying fluid mechanics have not been fully and correctly explained until recently and accurate characterization is required in determining how the flow triggers the downstream signalling cascades. Using the approximation of resistive force theory, we show how the flow is produced and calculate the optimal configuration to cause maximum flow, showing excellent agreement with in vitro measurements and numerical simulation, and paralleling recent analogue experiments. By calculating numerical solutions of the slender body theory equations, we present time-dependent physically based fluid dynamics simulations of particle pathlines in flows generated by large arrays of beating cilia, showing the far-field radial streamlines predicted by the theory.